2017
DOI: 10.3389/fnhum.2017.00202
|View full text |Cite
|
Sign up to set email alerts
|

GABA Concentrations in the Anterior Cingulate Cortex Are Associated with Fear Network Function and Fear Recovery in Humans

Abstract: Relapse of fear after successful treatment is a common phenomenon in patients with anxiety disorders. Animal research suggests that the inhibitory neurotransmitter γ-aminobutyric acid (GABA) plays a key role in the maintenance of extinguished fear. Here, we combined magnetic resonance spectroscopy and functional magnetic resonance imaging to investigate the role of GABA in fear recovery in 70 healthy male participants. We associated baseline GABA levels in the dorsal anterior cingulate cortex (dACC) to indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 59 publications
0
19
0
1
Order By: Relevance
“…Several lines of evidence have indicated that GABA concentrations in a variety of brain regions, including vmPFC (Jocham et al, 2012), amygdala (Levar et al, 2017), ACC (Northoff et al, 2007) and visual cortex (Muthukumaraswamy et al, 2009), predicted BOLD responses within the regions. Recent fMRI studies have shown that GABA level was inversely correlated with the strength of FC within motor and frontal-limbic networks (Delli Pizzi et al, 2017b; Levar et al, 2017; Stagg et al, 2014). It was suggested that higher GABA concentration in one region enhanced the inhibitory signaling within it (Delli Pizzi et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have indicated that GABA concentrations in a variety of brain regions, including vmPFC (Jocham et al, 2012), amygdala (Levar et al, 2017), ACC (Northoff et al, 2007) and visual cortex (Muthukumaraswamy et al, 2009), predicted BOLD responses within the regions. Recent fMRI studies have shown that GABA level was inversely correlated with the strength of FC within motor and frontal-limbic networks (Delli Pizzi et al, 2017b; Levar et al, 2017; Stagg et al, 2014). It was suggested that higher GABA concentration in one region enhanced the inhibitory signaling within it (Delli Pizzi et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, this area is responsible for the enhancement of contextual fear generalization after fear conditioning, and for the transfer of socially derived fear through its connections with the amygdala (Cullen et al 2015;Pisansky et al 2017;Allsop et al 2018). In humans, local GABAergic signaling in the ACC promotes fear extinction, which suggests that inhibition of the dorsal ACC may initially inhibit the retrieval of fear memories, and thus facilitates extinction learning (Levar et al 2017a(Levar et al , 2017b.…”
Section: Anterior Cingulate Cortexmentioning
confidence: 99%
“…In the case of PTSD, interestingly, the activation of ACC, together with the vmPFC and hippocampus, is sexually dimorphic: men with PTSD exhibited increased activation in the left rostral dACC during extinction recall compared to women with PTSD (Shvil et al 2014;Yoon et al 2017). Further, animal and human studies (Cullen et al 2015;Levar et al 2017aLevar et al , 2017b have positioned the ACC as an important hub to trigger fear retrieval alongside the PL, and its inhibition might be a way to boost fear extinction.…”
Section: Anterior Cingulate Cortexmentioning
confidence: 99%
“…Although it is much harder to assess excitation and inhibition in humans, the main contributors: Glutamate and GABA, can be accurately and reliably measured through Proton Magnetic Resonance Spectroscopy ( 1 H-MRS) [7][8][9]. Indeed, MRS-observed neurotransmitter levels reflect task-related activity with studies demonstrating sensitivity to baseline [10][11][12][13][14][15] and rapidly-modulating levels [16][17][18]. Most studies measured concentrations during rest and correlated it with later/previous behavior [13][14][15][19][20][21], yet some even measured during behavior [17,18,22].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies measured concentrations during rest and correlated it with later/previous behavior [13][14][15][19][20][21], yet some even measured during behavior [17,18,22]. A few studies have correlated baseline (rest) levels with subsequent/prior learning metrics [11,12,23], and one has even examined changes during motor learning [16]. However, none have quantified neurotransmitter modulations during active reinforcement-learning.…”
Section: Introductionmentioning
confidence: 99%